Desempenho de ovinos Santa Inês alimentados com níveis de proteína oriundas do resíduo de camarão em substituição a uma fonte protéica convencional - Santos, Marciliano de Melo (2010)
One of the main problems to reach good and productive results of sheeps for slaughtering relies on the quantity and quality of available food to such animals feeding. In the northeast, hay is short and of bad quality over drought period and when supplemented by traditional proteinic sources, the production cost is reasonably high. One viable alternative to solve such feeding deficiency is using agribusiness residues such as shrimp s wastes since this byproduct shows good feeding value especially concerning proteins. Such waste can be used to substitute soy in a lot of feeding systems, mainly in the confinement one. This waste presents low production cost decreasing total costs of confinement systems. One of the measures to evaluate the waste effect on sheeps feeding is analyze the performance of such animals under different levels of this waste addition and compare it to the traditional proteinic source (soy bren). This work was aimed at evaluating the Santa Inês sheeps performance fed with protein levels derived from shrimp waste in place of a conventional protein source.